Departure and consolation : the Johannine farewell discourses in light of Greco-Roman literature - Parsenios, George L. (Novum Testamentum, Supplements, 2005)
In contrast to the common opinion that the Johannine Farewell Discourses represent solely the Jewish genre of the Testament, George Parsenios argues that features of the discourses are misread or missed completely apart from Greco-Roman literature. Evidence from classical drama, for instance, assists in reading Jesus' return to the Father as a dramatic exit and, further, accounts for the puzzling delay of Jesus at 14:31 without recourse to redaction theories. Consolation literature and the literary symposium emphasize Jesus' continuing and consoling presence, with particular attention to the Paraclete's role as doppelgänger. The thread that binds the various chapters into a coherent whole, therefore, is the utility of classical literature in clarifying Jesus' consoling presence even after his departure to the Father.